Tinjauan Konstitualitas dan Studi Implementasi Kebijakan Bantuan Sosial Covid-19: Constitutional Review and Study on the Implementation of the Covid-19 Social Assistance Policy - Mikhael, Lefri; Nursanty, Riandini Yosandra Ira; Hananto, Mochamad Rifqi (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
COVID-19 pandemic devastated various sectors in public which impact on disturbance of the community welfare level. One of the government programs on guarantee proper standard of living including clothing, food, and shelter as well as improvement of proper living conditions in the pandemic period are through the COVID-19’s Social Assistance program by the Ministry of Social Affairs. The program is expected can solve the public problem during this pandemic period. Unfortunately there is some problems in the implementation. Which are about the constitutional issue of the program’s legal base nor technical issues in field, like the recipients of it’s social assistance are not in accordance with the intended purpose and others matters. The consequences of these problems have an impact on the effectiveness of this COVID-19’s Social Assistance program. The research aims to determine the suitability of the COVID-19’s Social Assistance’s policy within the framework of 1945’s Indonesian Constitution and its relation to citizen’s rights and the obligations of the government and also to identify this policy implementation that based on the implementation model Van Horn and Van Meter. The research was carried out in the form of qualitative research with literature study to collect the data. And also to identify the policy implementation that based on the implementation model of Van Horn and Van Meter. The research was carried out in the form of qualitative research with literature studies to collect the data. Briefly, the research shows that COVID-19’s Social Assistance’s program in line with State’s efforts to fullfil the basic rights of citizens, including a decent standard of living, especially during the COVID-19 pandemic and the implementation study with Van Horn Van Meter's variables, which are policy standards and objectives; policy resources; The implementor character; interorganizational communication and enforcement activities; the disposition of Implementors; and economic, social and political conditions indicates the success rate of COVID-19’s Social Assistance policy.